The Relationship Between Body Image, Emotional Maturity, and Rejection Sensitivity with Emotional Divorce in Women on the Verge of Divorce - Marvi, Masoumeh; Sadeghi, Elaheh; Samkhaniani, Eshagh (Mental Health and Lifestyle Journal, 2026)
The present study aimed to determine the relationship between body image, emotional maturity, and rejection sensitivity with emotional divorce among women on the verge of divorce in the city of Tonekabon. Given its primary purpose, this research was applied in nature and employed a correlational design. The statistical population consisted of all women on the verge of divorce in Tonekabon, which, according to data obtained from the Welfare Organization and the Social Emergency Center during 2022–2023, included 223 couples. A simple random sampling method was used to select participants. Based on the Krejcie and Morgan table, a sample of 136 married women was obtained. The research instruments included the Fisher Body Image Questionnaire (1970), the Emotional Maturity Scale by Yashvir Singh and Mahesh Bhargava (1991), the Rejection Sensitivity Questionnaire by Downey and Feldman (1996), and the Emotional Divorce Questionnaire by Gottman (2008). Data were analyzed using stepwise regression analysis with SPSS version 27. The findings indicated a significant relationship between body image, emotional maturity, and rejection sensitivity with emotional divorce among women. Moreover, the variables of rejection sensitivity, emotional maturity, and body image were found to have predictive power for the criterion variable of emotional divorce.